2013
DOI: 10.1155/2013/436502
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sleep to Hypertension: Greater Risk for Blacks

Abstract: Background. Evidence suggests that insufficient sleep duration is associated with an increased likelihood for hypertension. Both short (<6 hours) and long (>8 hour) sleep durations as well as hypertension are more prevalent among blacks than among whites. This study examined associations between sleep duration and hypertension, considering differential effects of race and ethnicity among black and white Americans. Methods. Data came from a cross-sectional household interview with 25,352 Americans (age range: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
1
21
2
Order By: Relevance
“…Event rates for hypertension were higher in Black subjects from the NHIS who were sleeping <6 hours/night or >8 hours/night, compared to their White counterparts 15 . These data are in line with findings from the Coronary Artery Risk Development in Young Adults (CARDIA) study 16 , where objective sleep duration, as quantified from actigraphy, related to greater surges in BP in African-Americans.…”
Section: Epidemiologic Evidencementioning
confidence: 82%
“…Event rates for hypertension were higher in Black subjects from the NHIS who were sleeping <6 hours/night or >8 hours/night, compared to their White counterparts 15 . These data are in line with findings from the Coronary Artery Risk Development in Young Adults (CARDIA) study 16 , where objective sleep duration, as quantified from actigraphy, related to greater surges in BP in African-Americans.…”
Section: Epidemiologic Evidencementioning
confidence: 82%
“…In the NHIS study, a stronger association between short and long sleep duration and diabetes, and short sleep duration and obesity was found in African American adults compared to non-Hispanic whites (34;35). Generally, more attention has been focused on short sleep duration as an adverse exposure, but long sleep duration has also been associated with race/ethnicity, cardiovascular and metabolic disease risk, and all-cause mortality, although these relationships are less well studied and understood (3638). A recent study by Hale et al found that fibrinogen partly mediated the association between long sleep duration and coronary heart disease and mortality in women, however, few studies have examined pathophysiology linking long sleep duration to disease risk or outcomes (39).…”
Section: 1 Sleep and Health Disparities Science: Emerging Opportunimentioning
confidence: 99%
“…Studies carried out in São Paulo show that 32% of São Paulo's citizens presented symptoms of insomnia 8 , as well as that, between 1987 and 2007, the percentage of paulistanos who had "trouble sleeping", "maintaining the sleep throughout the night" and "waking up" increased significantly 9 . Besides that, recent studies have identified an association between sleep disorders, metabolic and cardiovascular diseases (hypertension, dyslipidemia and diabetes mellitus) [10][11][12] , risk behaviors (smoking) 13,14 and the presence of overweight and/or obesity 15 . Sleep disorders, as well as the shorter duration of sleep, are associated to weight gain 16,17 , and the decrease in the quality of sleep seems to be associated to higher food intake and alcohol consumption 18 .…”
Section: Introductionmentioning
confidence: 99%